A randomized controlled trial comparing in-person and wiki-inspired nominal group techniques for engaging stakeholders in chronic kidney disease research prioritization. Issue 1 (December 2016) - Elliott, Meghan; Straus, Sharon; Pannu, Neesh; Ahmed, Sofia; Laupacis, Andreas; Chong, George; Hillier, David; Huffman, Kate; Lei, Andrew; Villanueva, Berlene; Young, Donna; Tam-Tham, Helen; et al.
Abstract Background Few studies have evaluated stakeholder engagement in chronic kidney disease (CKD) research prioritization. In this two-arm, parallel group randomized controlled trial, we sought to compare an in-person nominal group technique (NGT) approach with an online wiki-inspired alternative to determining the top 10 CKD research priorities, and to evaluate stakeholder engagement and satisfaction with each process. Methods Eligible participants included adults ≥18 years with access to a computer and Internet, high health literacy, and from one of the following stakeholder groups: patients with CKD not on dialysis, their caregivers, health care providers who care for patients with CKD, or CKD-related health policymakers. Fifty-six participants were randomized to a wiki-inspired modified NGT that occurred over 3 weeks vs. a 1-day in-person NGT workshop, informed by James Lind Alliance methodology, to determine the top 10 CKD-related research priorities. The primary outcome was the pairwise agreement between the two groups' final top 10 ranked priorities, evaluated using Spearman's correlation coefficient. Secondary outcomes included participant engagement and satisfaction and wiki tool usability. Results Spearman's rho for correlation between the two lists was 0.139 (95 % confidence interval −0.543 to 0.703, p = 0.71), suggesting low correlation between the top 10 lists across the two groups. Both groups ranked the same item as the top research priority, with 5 of the top 10 priorities ranked by the wiki group within the top 10 for the in-person group. In comparison to the in-person group, participants from the wiki group were less likely to report: satisfaction with the format (73.7 vs.100 %, p = 0.011); ability to express their views (57.9 vs 96.0 %, p = 0.0003); and perception that they contributed meaningfully to the process (68.4 vs 84.0 %, p = 0.004). Conclusions A CKD research prioritization approach using an online wiki-like tool identified low correlation in rankings compared with an in-person approach, with less satisfaction and perceptions of active engagement. Modifications to the wiki-inspired tool are required before it can be considered a potential alternative to an in-person workshop for engaging patients in determining research priorities. Trial registration (ISRCTN18248625 )